Application of a hybrid method in disaster prevention and relief evaluation - Chun Chu Liu; Tse Yu Wang (Technological and Economic Development of Economy, 2019)
The purpose of this study is to propose a hybrid method for disaster prevention and relief (DPR) evaluation for Taiwan. Through the hybrid method and evaluation results, the central and local governments of Taiwan could continuously improve and strengthen their DPR system. The main structure of the evaluation is based on the balanced scorecard (BSC), and 15 indicators are gathered from the literature on related issues. These indicators are further analyzed by data envelopment analysis (DEA) and the Malmquist productivity index (MPI) to assess the DPR efficiency of 13 administrative regions in Taiwan. The analysis shows that the DPR system in Taiwan might be improved in Yunlin and Hsinchu City, two administrative regions analyzed during the three stages and time frame studied. The indicators that most significantly affect DPR efficiency are the average number of people served by each government employee or teacher (L1), the supervision score of the Department of Medical Services (DMS) of the Ministry of Health and Welfare (I4), the number of licensed medical practitioners per 10,000 people (C1) and the number of social welfare workers per 10,000 people (C2). These indicators also reflect Taiwan's current shortages in DPR-related and medical personnel.